已知列表x = [1, 2],那么执行语句x.extend([3]) 之后, x的值为___()_______。
A: [[1], [2]]
B: [1, 2, 3]
C: [3, 1, 2]
D: [1, 2, [3]]
A: [[1], [2]]
B: [1, 2, 3]
C: [3, 1, 2]
D: [1, 2, [3]]
举一反三
- 已知列表 x = ['1', '2'],那么执行语句 x.append(['3']) 之后,x 的值为 ( ) A: ['1', '2', '3'] B: ['1', ''2, ['3']] C: ['1'] D: ['3']
- 已知 x = [1, 2],那么执行语句 x[0:0] = [3]*2之后,x的值为___________。 A: [[3], [3], 1, 2] B: [[3, 3],1, 2] C: [3, 1, 2] D: [3, 3, 1, 2]
- 已知列表 x = [1, 2,3],那么执行语句 x.append([3]) 之后,x的值为_____________。 A: [1, 2,3,[3]] B: [1, 2,3,3] C: [1, 2,[3]] D: 1,2,3,[3]
- 已知列表 x = [1, 2, 3],那么执行语句 x.insert(1, 4) 之后,x的值为___________。 A: [4, 1, 2, 3] B: [1, 4, 2, 3] C: [1, 2, 3, 4] D: [1, 1, 2, 2]
- 已知列表x = [1, 2],那么执行语句 x.extend([3])之后,x的值为[1, 2, 3] A: 正确 B: 错误